A Site of Shifting Boundaries: Fostering and Limiting Mobility in the Ruhr Valley (1860–1910). Issue 4 (8th August 2019) - Friedrichs, Anne
ABSTRACT: In recent decades, our perception of borders has become increasingly complex: 30 years after the Schengen Agreement, EU citizens' freedom to travel is largely taken for granted, yet contemporary debates on refugees and the external borders of the European Union suggest that borders resemble semi-permeable membranes, enabling the influx of "desired" persons while excluding "undesirable" migratory flows. However, these trends in "filtering" movements of people are hardly unique to the 21 st century. This article treats the Ruhr Valley as an example of early migration to Germany and the associated rights and restrictions placed on movement there in the second half of the "long" 19 th century. The author argues that limits on migration and settlement also shifted in zones of increasing mobility and migration like the Ruhr region, where they excluded Russian "Poles" in particular. However, migration control by the higher authorities was never total. The paper first shows how the actions of different groups (political authorities, entrepreneurs, migrants, and their networks) were intertwined with one another in a way that made the Ruhr region into a preferred destination for migrants within a transatlantic migration system. It then critically analyzes the hitherto little discussed expulsions and naturalization procedures as political means of population control and illuminates the importance of latent divergent interests at different levels of government. Overall, the study intends to contribute to a better understanding of the different social mechanisms on the local level that were part of migration control in the context of the nascent (nation) state.